Cheney Lake Watershed: Conservation Practice Implementation History and Trends - Devlin, Daniel; Miller, Howard; Nelson, Nathan; Barnes, Philip; French, Lisa; Frees, Lyle (My University, 2008)
The Cheney Lake Watershed in south-central Kansas has been the focus of multiple water quality related research, extension, and education projects for approximately 15 years.
EP157_2008-11
Keywords: EP157; Environment and Natural Resources; EP